NEUROPROTECTION OF ABELMOSCHUS ESCULENTUS L. AGAINST DIABETIC NEUROPATHY - Yang, Lee Wei; Fattepur, Santosh; Nilugal, Kiran Chanabasappa; Asmani, Fadli; Yusuf, Eddy; Ghani, Mohd Nizam Abdul; Abdullah, Ibrahim (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study was designed to determine the neuroprotective effect of Abelmoschus esculentus L. on alloxan-induced diabetic neuropathy in rats. Methods: Diabetes was induced in rats with a single intraperitoneal injection of alloxan monohydrate (130 mg/kg b.w). The ethanol extract of A. esculentus L. at a dose of 100 and 200 mg/kg of body weight was administered at single dose per day to alloxan-induced diabetic rats for 21 days. The fasting blood glucose was screened in the intermittent on day 0, day 14, and day 21. Behavioral tests such as thermal hyperalgesia test and rotarod performance test were performed to assess the thermal sensitivity and muscle grip strength. At the end of the study period, experimental animals were sacrificed and sciatic nerve tissues were obtained for histopathological investigation. Results: Animals treated with A. esculentus L. extarct at a dose of 200 mg/kg of body weight significantly reduced (p<0.05) in hyperglycemia and thermal hyperalgesia and significantly increased (p<0.05) in rotarod performance. The sciatic nerve fiber of diabetic rats receiving 200 mg/kg of body weight of A. esculentus L. extract also shows no swelling of nerve fibers, and lesser demyelination was observed. Conclusion: These findings demonstrate that A. esculentus L. exhibits significant antidiabetic and neuroprotective effect against alloxan-induced diabetic neuropathy in rats.